Estudo da estimulação elétrica nervosa transcutânea em modelo experimental de hiperalgesia induzida pela carragenina - George Schayer Sabino (2007)
Transcutaneous electric nerve stimulation (TENS) is a noninvasive treatment used in physiotherapy practice to promote analgesia in acute and chronic inflammatory conditions. The aim of the present study was to investigate the action mechanism of TENS at high (HF:130Hz) and low (LF:10Hz) frequencies in an inflammation model produced by the injection of carrageenan in rat paws (Cg; 250µg). Following carrageenan administration (zero time), either HF or LF TENS was applied to the inflamed paw of the rat for 20 minutes and hyperalgesia was assessed hourly using the modified Randall-Selitto method (1957). HF and LF TENS inhibited the carrageenan-induced hyperalgesia by 100%. However, LF TENS presented a longer- lasting analgesic effect than HF TENS. Pre-treatment of animals with intraplantar naltrexone (Nx; 50 µg) reversed the analgesic effect of the LF TENS, but did not alter the effect of HF TENS. The application of HF and LF TENS in the contralateral paw reversed the hyperalgesia of the inflamed paw at the same extent as ipsilaterally. Our data demonstrate that HF and LF TENS induced antinociception when applied on the ipsi or contralateral inflamed side and that the antinociception provoked by LF TENS is partially due to the local release of endogenous opiods.